Relationships between Sea Surface Temperature (SST) and rainfall distribution pattern in South-Central Java, Indonesia - Bayu Dwi Apri Nugroho (Faculty of Geography, Universitas Gadjah Mada, 2015)
Although there has been a high relationship between global climate and rainfall in Indonesia, little evidence is available for relationship between Sea Surface Temperature (SST) and rainfall pattern in highland of country. This study evaluates the relationships between Sea Surface Temperature (SST) and rainfall distribution pattern in Gunungkidul district, highland of South-Central Java, Indonesia. Principal Component Analysis (PCA) approach was used to summarize the average of SSTs during rainy season (October to March) for the El Niño monitoring regions: IOBW (Indian Ocean Basin-Wide), Niño.West and Niño.3. Monthly rainfall data was collected from Agricultural Government of Gunungkidul district. In this area, rainfall was highest in the southern and western mountainous areas, especially near the coast, and SSTs values were highly correlated with rainfall in those areas. Almost all sub districts in Gunungkidul district has significant correlations between PC1 SSTs and rainfall during October-November-December (OND).